1983
DOI: 10.3109/15513818309025870
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiomas of the Umbilical Cord

Abstract: Four cases of umbilical cord hemangioma are presented and analyzed with all previously reported cases. Umbilical cord hemangiomas consist of an angiomatous nodule containing and encompassed by edema and myxomatous degeneration of Wharton's jelly, often cystic. The angiomatous nodules range from 0.2 to 7 cm in largest dimension, whereas the associated edema may measure up to 15 cm. The tumors tend to occur at the placental end of the cord and presumably arise from one or more of the major umbilical vessels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
4

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 15 publications
2
39
0
4
Order By: Relevance
“…4 Potential fetal long-term complications of cord angiomyxomas include vascular compression of the main cord vessels with abnormal growth and possible intrauterine death. 1 Raised maternal serum alpha-fetoprotein, as in the present case, can be the earliest prenatal clue to the development of a cord angiomyxoma. 4 When the fetus appears structurally normal, placental chorioangioma (which has a different prognosis 5 and is also associated with raised levels of alpha-fetoprotein 6 ) must be excluded.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…4 Potential fetal long-term complications of cord angiomyxomas include vascular compression of the main cord vessels with abnormal growth and possible intrauterine death. 1 Raised maternal serum alpha-fetoprotein, as in the present case, can be the earliest prenatal clue to the development of a cord angiomyxoma. 4 When the fetus appears structurally normal, placental chorioangioma (which has a different prognosis 5 and is also associated with raised levels of alpha-fetoprotein 6 ) must be excluded.…”
Section: Discussionsupporting
confidence: 53%
“…1 We are not aware of another case in which the entire length of the cord was infiltrated by angiomatous tissue. Theoretically, cord angiomyxoma may arise from one or more umbilical vessels or from remnants of embryonic vessels.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hemangioma of the umbilical cord is characterized by welldefined aggregates of closely packed, thin-walled capillary proliferation originating from the umbilical arteries, the umbilical vein or vitelline capillaries [7]. The etiology is still not clear; it may represent a true neoplasm or it may be a developmental abnormality (hamartoma).…”
Section: Hemangioma Of the Umbilical Cordmentioning
confidence: 99%
“…Most often hemangioma is an isolated anomaly, but large lesions have been described in association with polyhydramnios [2], intrauterine growth retardation, elevated maternal serum alpha-fetoprotein [9] and fetal malformations [2]. Some authors have also reported its association with premature delivery and even with fetal death caused by impaired umbilical circulation resulting in nonimmune hydrops fetalis [4], torsion, compression, or stenosis of the umbilical vessels, fetal hemorrhage [7], thrombosis of an umbilical vessel and hematoma of the umbilical cord [11]. We reviewed 37 reports in the literature from 1951 through 2005, in most of which the lesion was referred to as hemangioma, and rarely as angiomyxoma, myangioma or hemangiofibromyxoma because of the myxoid appearance of the commonly associated edematous degeneration of the Wharton's jelly.…”
Section: Hemangioma Of the Umbilical Cordmentioning
confidence: 99%